Retrieved Optical Thickness for Analyzing The Aerosol and Cloud Properties Using Lidar Remote Sensing - Dewang, Syamsir (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2010)
The lidar remote sensing is the one important application to observe the aerosol and cloud of the atmosphere. Themicropulse lidar (MPL) return signals were studied in the tropical area. In this investigation, the single scatteringis analyzed by the physical properties of aerosol and cloud. The signal simulation of the single scattering predictsthe maximum optical thickness by saturation. It was observed that saturation optical thickness from the lidarsignal depends on the variation of extinction coefficient. This simulation is compared by the optical thicknessestimation from the lidar data. The MPL data (at wavelength of 523 nm) was determined, and the sky radiometer (atwavelength 500 nm) was used as reference data. The maximum optical thickness of lidar was 2.6 at night time,and the maximum optical depth of lidar and sky radiometer data on the same day were 2.25 and 1.7, respectively.